PERILAKU IBU TERHADAP KEBUTUHAN GIZI SEIMBANG BAGI BALITA DI DUSUN II DESA SEI LIMBAT KECAMATAN SELESAI KABUPATEN LANGKAT TAHUN 2021 - KAMALIAH . (JURNAL ILMIAH SIMANTEK, 2022)
Every child has the right to live, grow, develop and participate reasonably, protected from violence and discrimination.They are also entitled to health and social security services in accordance with physical, mental, spiritual and social needs,as stated in Child Protection Law No. 23 of 2002. Toddlers are children aged 0-59 months, at this time characterized by avery rapid process of growth and development, accompanied by changes that require more nutrients with high quality.Monitoring of toddler growth should still be implemented through various alternative efforts to ensure toddlers are nutritionallybalanced for their developmental and growth needs. The purpose of this study was to find out the mother's behavior towardsbalanced nutritional needs in toddlers. This study is deskrictive by using primary data and secondary data obtained throughinterviews of respondents using questionnaires where the sample number is as many as 80 respondents. Data that has beencollected, processed by providing values and presented using distribution tables. Based on the results of this study showedthat, the majority of respondents are quite knowledgeable, namely as many as 25 respondents (40.32%), a well-roundedminority of respondents, which is as many as 15 respondents (24.19%). The majority of respondents were negative, with 41(66.13%), the minority being positive, with 21 respondents (33.87%). The majority did not take action, namely as many as 39respondents (62.91%), and the minority who took action, namely as many as 23 respondents (37.09%). It is expected to thecommunity to pay attention to the nutritional needs of toddlers by frequent consultation with health workers in order to gainknowledge about balanced nutritional needs in toddlers, so that toddlers' nutritional needs will be met.